2012
DOI: 10.1007/s12298-012-0122-x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical effect of 24-epibrassinoslide on cold tolerance in maize seedlings

Abstract: Germination and early seedling growth are important for establishment of maize because maize is chilling sensitive crop and low temperature during early period of growth can be detrimental to subsequent crop growth and productivity. Therefore, it is important to protect maize seedling from cold stress. A study was conducted on induced cold tolerance by 24-epibrassinoslide (EBR) at the Indian Agricultural Research Institute, New Delhi, India. Maize seedlings were raised in green house condition (25/18°C day-nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Among the treatments, T2 had the best effect, and there were differences between the different varieties, with various degrees of cold resistance. This is similar to previous studies [59,62]. In this study, it was found that the photosynthesis-related indicators of the maize variety with stronger cold resistance were less changed.…”
Section: Protective Effects Of Blsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the treatments, T2 had the best effect, and there were differences between the different varieties, with various degrees of cold resistance. This is similar to previous studies [59,62]. In this study, it was found that the photosynthesis-related indicators of the maize variety with stronger cold resistance were less changed.…”
Section: Protective Effects Of Blsupporting
confidence: 92%
“…Xu [58] and others have shown that BL can effectively alleviate the decrease in cucumber biomass caused by low temperature and can enhance the ability to resist chilling stress, by regulating the physiological metabolism of cucumber, thereby promoting the accumulation of dry matter [59]. The same conclusions have been corroborated in crops such as maize, rice and wheat [11,[60][61][62]. Within the experimental range, the foliar spraying of three concentrations (T1, T2, T3) of BL solution significantly reduced the inhibitory effects maize seedlings caused by low temperature, and the T2 treatment effect was the most significant.…”
Section: Protective Effects Of Blmentioning
confidence: 73%
“…In this study, we focused on BR and GA control of seedling traits, as BR and GA promote seedling vigor and growth (Fuchs and Lieberman, 1968;Evans and Poethig, 1995;Clouse, 2001;Özdemir et al, 2004;Ashraf et al, 2010) and they are positively correlated to seedling stress tolerance of drought, salinity, cold/heat, and heavy metals in different plant species such as maize, sorghum, Arabidopsis and rice (Anuradha and Rao, 2001;Vardhini and Rao, 2003;Kagale et al, 2007;Colebrook et al, 2014). For example, exogenous application of BRs increased the cold tolerance of maize seedlings (Singh et al, 2012), and increased endogenous levels of GAs were effective in protecting maize seedlings from drought stress For both DHB47 and DHZ51, shoot length, mesocotyl length, and primary root length were reduced with the application of BR and GA inhibitors compared to water treatment. BRM, BRS, GAM and GAS was below 1.0 for all the 207 BGEM lines except for one line BGEM-0123-N with BRS equal to 1.1.…”
Section: Discussionmentioning
confidence: 99%
“…Both dry and wet weights for seedling roots and shoots were measured because while both are indices of size, wet weight additionally reflects tissue water content, which is generally relevant to seedling health and performance (e.g. Ping et al ., ; Zygielbaum et al ., ; Singh et al ., ). A total of 34 Balsas teosinte seedling pairs (Guachinango = 13, San Lorenzo = 11 and El Cuyotomate = 10), 47 landrace maize pairs (Tuxpeño = 16, Tepecintle = 15 and Olotón = 16 ) and 44 maize inbred line pairs (B73 = 16, CML176 = 15 and MP708 = 13 ) were evaluated as described above.…”
Section: Methodsmentioning
confidence: 99%